Social development : the developmental perspective in social welfare - Midgley, James (Sage, 1995)
The social development approach seeks to integrate economic and social policies within a dynamic development process in order to achieve social welfare objectives. This comprehensive textbook demonstrates that social development offers critically significant insights for the developed as well as the developing world.